Jose Rizal the man, the hero, the Filipino - Chiu, Stella; Nolasco, Butch; The Bookmark (Makati City: The Bookmark Inc. and the Department of History of the Ateneo De Manila University, 1999)
Rizal, a genius and writer, whose books inspired the Philippine Revolution against Spain in 1896-1898, died before a Spanish firing squad in 1896. In the film Rizal looks back on the events in his life and comments on episodes in his writings
Copy available in DVD format
Executive producer, Jose Ma Lorenzo Tan
VHS Format
Keywords: Rizal, Jose, -- 1861-1896